Investigating the spatiotemporal dynamic evolution and driving factors of wastewater treatment efficiency in the context of China’s River Chief system - Zhang, Zhengxian; Li, Yun; Wang, Xiaogang; Xu, Yuan; Liao, Yipeng; Wan, Zhiyong; Tang, Nanbo (Ecological indicators, 2021)
[Display omitted] •Investigating the urban wastewater governance under the context of China's River Chief system.•Quantifying the spatiotemporal distribution and driving effects in wastewater governance efficiency.•The SBM-DEA model with undesirable outputs and LMDI decomposition model are developed.•Wastewater treatment efficiency is improved through the implementation of China's River Chief system. Investigating the wastewater treatment efficiency (WTE) is an important component in fostering sustainable water management. This study proposes an environmental production technology framework based on eutrophication levels and heavy metal concentrations caused by wastewater discharge. The slack based measure (SBM) model with undesirable outputs and logarithmic mean Divisia index (LMDI) decomposition model are developed to quantitatively investigate the spatiotemporal distribution and driving effects in urban wastewater treatment under the context of China's River Chief system. Results showed that the distribution curve of WTE changes from double peaks to a single peak, and WTE value appears a decreasing (2001–2010)-increasing (2011–2020) trend. Provinces with high WTE are mainly distributed in eastern China, with low WTE are in western China. Overall, wastewater treatment efficiency has been generally improved through the implementation of China’s River Chief system. And provinces with low WTE are shrinking, with high WTE are extending from southeastern to northwestern China. To achieve a simultaneous improvement in wastewater treatment efficiency, it is necessary to improve the WTE in corresponding provinces that belong to barely effective development and inefficient development. Meanwhile, provinces in superiorly effective development and slightly effective development should be encouraged to maintain their high-level WTE.